Factors affecting number of lymph nodes harvested and the impact of examining a minimum of 12 lymph nodes in stage I-III colorectal cancer patients: a retrospective single institution cohort study of 1167 consecutive patients. Issue 1 (December 2016) - Tsai, Hsiang-Lin; Huang, Ching-Wen; Yeh, Yung-Sung; Ma, Cheng-Jen; Chen, Chao-Wen; Lu, Chien-Yu; Huang, Ming-Yii; Yang, I-Ping; Wang, Jaw-Yuan
Abstract Background To identify factors affecting the harvest of lymph nodes (LNs) and to investigate the association between examining a minimum of 12 LNs and clinical outcomes in stage I-III colorectal cancer (CRC) patients. Methods The clinicopathologic features and the number of examined LNs for 1167 stage I-III CRC patients were analyzed to identify factors affecting the number of LNs harvested and the correlations between clinical outcomes and high harvests (≧12 LNs) and low harvests (<12 LNs). Results A multivariate analysis showed that age (P = 0.007), tumor size (P = 0.030), and higher T stage (P = 0.001) were independent factors affecting the examinations of LNs in colon cancer and that tumor size (P = 0.015) was the only independent factor in rectal cancer. Patients with low harvests had poorer overall survival with stage II and stage III CRC (stage II:P < 0.0001; III:P = 0.001) and poorer disease-free survival for stages I-III (stage I:P = 0.023; II:P < 0.0001; III:P = 0.001). Conclusions The factors influencing nodal harvest are multifactorial, and an adequate number of examined LNs (≧12) is associated with a survival benefit. Removal of at least 12 LNs will determine the lymph node status reliably.